2012
DOI: 10.1093/jjco/hys033
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Interstitial Lung Disease During Everolimus Treatment in Patients with Metastatic Renal Cell Carcinoma

Abstract: Serum Krebs von den Lungen 6 was elevated compared with baseline in all cases with interstitial lung disease. Some patients who developed mild interstitial lung disease during everolimus treatment could continue to receive the treatment. Even when severe interstitial lung disease developed, withdrawal of the drug and short-term use of high-dose steroids resulted in rapid recovery. Prompt recognition of interstitial lung disease exacerbation as well as exclusion of progressive disease or infection is of primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 16 publications
2
27
0
3
Order By: Relevance
“…In vivo studies have also shown that rapamycin treatment augments lung injury induced by BLM or lipopolysaccharide in mice with acute lung injury (17,28). Clinically, serum Krebs von den Lungen 6, which is a biomarker of interstitial lung disease and is associated with epithelial cell injury and capillary-alveolar permeability changes, is elevated in patients with everolimus-induced ILD (24,34). Based on these data, it is speculated that mTOR inhibitors have the potential to cause alveolar epithelial injury, which could, in turn, initiate and/or augment lung injury (as shown in the left pathway in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have also shown that rapamycin treatment augments lung injury induced by BLM or lipopolysaccharide in mice with acute lung injury (17,28). Clinically, serum Krebs von den Lungen 6, which is a biomarker of interstitial lung disease and is associated with epithelial cell injury and capillary-alveolar permeability changes, is elevated in patients with everolimus-induced ILD (24,34). Based on these data, it is speculated that mTOR inhibitors have the potential to cause alveolar epithelial injury, which could, in turn, initiate and/or augment lung injury (as shown in the left pathway in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among the previous studies of everolimus-induced ILD written in English, we could find only nine articles that described the pathological findings of ILD (1,(11)(12)(13)(14)(15)(16)(17)(18). Table 3 presents descriptions of the pathological findings of everolimus-induced ILD in these nine articles, which included 13 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Everolimus was used for the treatment of advanced RCC, and PNET. The frequencies of ILD related to everolimus ranged from 8 to 14% of treated patients [36][37][38][39][40][41][42]. The mortality rate due to ILD was reported to be 3.8% (4 of 105 patients) in a previous study [4].…”
Section: Mammalian Target Of Rapamycin (Mtor) Inhibitorsmentioning
confidence: 97%